2014
DOI: 10.1155/2014/620434
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Preclinical Evaluation of New Thiazolidin-4-ones Substituted with p-Chlorophenoxy Acetic Acid and Clofibric Acid against Insulin Resistance and Metabolic Disorder

Abstract: We synthesized twenty thiazolidin-4-one derivatives, which were then characterized by standard chromatographic and spectroscopic methods. From the in vitro glucose uptake assay, two compounds behaved as insulin sensitizers, where they enhanced glucose uptake in isolated rat diaphragm. In high-carbohydrate diet-induced insulin resistant mice, these two thiazolidin-4-ones attenuated hyperglycemia, hyperinsulinemia, hypertriglyceridemia, hypercholesterolemia, and glucose intolerance. They raised the plasma leptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Consistent with a previous report, our study also revealed that exercise upregulated the reduction of total plasma SCFAs in DM mice. Previous evidence has shown that acetic acid improves muscle glucose uptake, reduces hyperglycemia in diabetic mice and its derivatives are confirmed to treat IR and T2DM [54,55]. Of note, the changes we presented in total plasma SCFAs were mainly highlighted in plasma acetic acid.…”
Section: Discussionsupporting
confidence: 62%
“…Consistent with a previous report, our study also revealed that exercise upregulated the reduction of total plasma SCFAs in DM mice. Previous evidence has shown that acetic acid improves muscle glucose uptake, reduces hyperglycemia in diabetic mice and its derivatives are confirmed to treat IR and T2DM [54,55]. Of note, the changes we presented in total plasma SCFAs were mainly highlighted in plasma acetic acid.…”
Section: Discussionsupporting
confidence: 62%
“…In the present study, combined administration of MSG and HSu clearly induced MetS, characterized by increased body weight, hyperglycemia, hypertriglyceridemia, and glucose intolerance, along with significant hypoalphalipoproteinemia. Further, the model used in the present study exhibited early body weight gain compared with previously reported models of MSG or a high‐calorie diet alone. Male rats had greater weight gain (from Week 6 onwards) than female rats (from Week 17 onwards).…”
Section: Discussionsupporting
confidence: 51%
“…Earlier work in our laboratory demonstrated the antidiabetic and hypolipidemic effects of thiazolidin‐4‐one derivatives (100 mg/kg doses) possessing a nicotinamide (NAT1) or p ‐chlorophenoxyacetamide (PAT1) substitution at the N3 position of the thiazolidinone ring (Fig. ).…”
Section: Introductionmentioning
confidence: 95%
“…In the HCD study, blood was collected from the tail vein of each mouse and subsequently centrifuged for 10 min, at 3000× g , 4 °C; plasma was stored at −20 °C for assay of insulin and glucose levels as previously reported [ 27 , 33 ]. Plasma glucose was measured spectrophotometrically using commercially available colorimetric kits (Aspen Laboratories Pvt.…”
Section: Methodsmentioning
confidence: 99%